08.08 Podocytes internalise dna-antibody complexes. (1st March 2017) - Römer-Hillmann, Anja; Jung, Elisabeth; Engbers, Annika; Reinhardt, Marcel; Wardemann, Hedda; Pap, Thomas; Jacobi, Annett
Abstract : Background: Podocytes are postmitotic visceral epithelial cells, located at the Bowmans capsule of the kidney building up the slit diaphragm with their foot processes to filtrate the blood and keep valuable large proteins in the vessels. In Systemic Lupus Erythematosus (SLE) different organs are affected by autoantibodies which results in chronic inflammation and a high percentage of patients develop Lupus nephritis (LN) resulting in podocyte damage and disruption of the slit diaphragm. The risk for LN correlates directly with the level of anti-double stranded DNA antibodies (adsDNAabs). In this study, we wanted to identify the direct effect of adsDNAabs on podocytes. Methods: We established an in vitro system to investigate the specific impact of monoclonal antibodies and their immune complexes directly on podocytes (AB8 cell line). Monoclonal antibodies were generated by transfecting HEK293T cell line with Ig heavy and corresponding light chain encoding plasmid DNA obtained from single B cells of patients with SLE and LN. Podocytes were incubated with the produced monoclonal antibodies and the internalisation process and functional consequences were analysed by immunofluorescence, Western Blot, FACS and electron microscopy. For comparison, primary human podocytes were isolated from LN patient urine and analysed by immunofluorescence. Results: The recombinantly produced adsDNAabs from LN patients were specific against nuclear structures and build complexes with double stranded DNA, essential for the internalisation by cultivated podocytes. Interestingly, viability and migratory capacity were not influenced by the exposure to adsDNAabs for 48 hour. The internalised antibodies were enclosed by membranous structures and reach the cytosol via clathrin dependent endocytosis. The process of internalisation was time and dose dependent and reversible. Furthermore, internalised antibody complexes could also be detected in primary human LN podocytes. Conclusion: In our in vitro model the specific uptake of adsDNAabs was observed, in line with human LN data. Podocytes from patients with LN show IgG positive aggregates in the cytosol. The internalisation depends on the complex formation of the antibodies with dsDNA and could be important part of the LN pathogenesis.